Students' Attitudes and Perceptions towards Learning EAP Courses during Emergency Remote Teaching: Insights and Implications - Inna Smirnov-Okanin; Roman Michaelan; Sonia C. Munteanu; Sanda Păduretu (Research in Language)
Against the backdrop of the COVID-19 pandemic in the middle of the spring 2020 semester, many high education institutions were forced to move from face-to-face (FTF) teaching to remote instruction. The purpose of this study is to investigate students' attitudes and perceptions towards their learning of English for academic purposes mandatory courses and their engagement in learning these courses in comparison to FTF learning. The subjects of the research consisted of 712 students from two engineering higher education institutions (one from Romania and one from Israel) and one general higher education institution from Israel. Data were collected using a 5-point Likert-type survey. The results indicated that students had a positive attitude towards the remote learning of English and perceived it as having a positive effect on their learning experience and engagement. The results of the research can help educators in terms of adopting appropriate decisions regarding online teaching as a routine mode of learning (not in the emergency) and to make appropriate modifications and adaptations to the EAP courses. Thus, a better understanding of how this transition impacts students' attitudes toward learning could have important implications for instructional design, curriculum development, and teacher training.